Design and application of a novel device for recovering and storing gastric juices (一种新型胃液回收及存储装置的设计与应用) - WANG Weiwei (王伟伟); ZHANG Meng (张萌); SUN Xiumei (孙秀梅) (中西医结合护理)
Enteral nutrition is the preferred method of nutritional support for critically ill patients. Gastric residual volume monitoring can well assess gastrointestinal motility and enteral nutrition tolerance, and is also the most commonly used indicator to identify high aspiration risk. At present, syringe withdrawal is the most commonly used method to monitor gastric residual volume. This paper introduces the design and use method of a utility model gastric fluid recovery and storage device, which can effectively reduce the occurrence of secondary pollution, reduce the work burden of medical staff and improve work efficiency. (肠内营养是重症患者营养支持的首选方法, 胃残余量监测能够很好的评估胃肠动力和肠内营养的耐受情况, 也是识别高误吸风险最常用的指标。目前注射器回抽法是临床监测胃残余量最常用的方法。本研究介绍了一款实用新型胃液回收及存储装置的设计和使用方法, 旨在有效降低二次污染的发生风险, 同时减轻医护人员的工作负担, 提高工作效率。)